Digital economy and society in Hungary and Ukraine - Szabolcs, Nagy (НТУ "ХПІ", 2017)
We live in the Digital Age in which both economy and society have been transforming significantly. The Internet and the connected digital devices are inseparable parts of our daily life and the engine of the economic growth. In this paper, first I analyzed the status of digital economy and society in Hungary, then compared it with Ukraine and made conclusions regarding the future development tendencies. Using secondary data provided by the European Commission I investigated the five components of the Digital Economy and Society Index of Hungary. I performed cross country analysis to find out the significant differences between Ukraine and Hungary in terms of access to the Internet and device use including smartphones, computers and tablets. Based on my findings, I concluded that Hungary is more developed in terms of the significant parameters of the digital economy and society than Ukraine, but even Hungary is an emerging digital nation. Considering the high growth rate of Internet, tablet and smartphone penetration in both countries, I expect faster progress in the development of the digital economy and society in Hungary and Ukraine.

У даній роботі я вперше проаналізував стан цифрової економіки та суспільства в Угорщині, потім порівняв його з Україною та зробив висновки щодо майбутніх тенденцій розвитку. Використовуючи вторинні дані, надані Європейською комісією, я досліджував п'ять компонентів Індексу цифрової економіки та суспільства Угорщини. Я провів аналіз крос-країни, щоб з'ясувати суттєві відмінності між Україною та Угорщиною щодо доступу до Інтернету та використання пристроїв, включаючи смартфони, комп'ютери та планшети. Виходячи з моїх висновків, я зробив висновок, що Угорщина більш розвинена з точки зору значущих параметрів цифрової економіки та суспільства, ніж Україна, але навіть Угорщина є новою цифровою нацією. Враховуючи високі темпи зростання інтернет-прояву планшета та смартфонів в обох країнах, я очікую більш швидкого прогресу у розвитку цифрової економіки та суспільства в Угорщині та Україні.
Цифрова економіка та суспільство в Угорщині та Україні
Keywords: Internet; device usage; cross country comparison; ICT; інтернет; використання пристроїв